Adsorption of Anionic Dyes on Boron Industry Waste in Single and Binary Solutions Using Batch and Fixed-Bed Systems - Atar, Necip; Olgun, A.; Wang, Shaobin; Liu, Shaomin (American Chemical Society, 2011)
The removal of Acid Red 183 (AR183) and Reactive Blue 4 (RB4) from single and binary solutions onto a waste material (WM) from the boron industry was studied. The adsorption capacities of AR183 and RB4 on WM in single dye solutions were found to be 9.11·10−5 mol·g−1 and 7.33·10−5 mol·g−1, respectively. Because of competitive adsorption, the adsorption capacities in binary solutions were reduced to 7.43·10−5 mol·g−1 and 6.37·10−5 mol·g−1, respectively. The adsorption followed pseudosecond-order kinetics, and the isotherm fit well to the Langmuir model. In column experiments, the adsorption of dyes from single and binary solutions was fit well by the Thomas model. The breakthrough and exhaustion capacity of each dye decreased with increasing flow rate and decreaed in the presence of the other dye. The thermodynamic parameters such as Gibbs energy change (ΔG), entropy change (ΔS), and enthalpy change (ΔH) were obtained, showing the exothermic nature of dye adsorption on WM.